2020
DOI: 10.1101/2020.11.27.401778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Jack-of-all-trades paradigm meets long-term data: generalist herbivores are more widespread and locally less abundant

Abstract: Some of the most common ecological interactions are between plants and herbivorous insects, and these relationships are central to the study of ecological specialization. We address established assumptions about the positive association between local abundance and dietary specialization using a 17-year dataset on the caterpillars of Ecuador. Our long-term data include standardized plot-based samples as well as general, regional collections, allowing for investigations across spatial scales and using different … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…In this study, we demonstrated the larger and less abundant species have higher dispersal patterns and broader diet breadths compared to their smaller relatives. These associations corroborate the evidence found in a long-term study from Ecuador, in which generalist species are widespread and locally less abundant [18,19,20]. Further studies are required to confirm the causal mechanisms operating to generate the observed patterns, and to test the correlations between fine-scale movements and large-scale dispersal.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In this study, we demonstrated the larger and less abundant species have higher dispersal patterns and broader diet breadths compared to their smaller relatives. These associations corroborate the evidence found in a long-term study from Ecuador, in which generalist species are widespread and locally less abundant [18,19,20]. Further studies are required to confirm the causal mechanisms operating to generate the observed patterns, and to test the correlations between fine-scale movements and large-scale dispersal.…”
Section: Discussionsupporting
confidence: 78%
“…From these studies, the common expectation is that "a jack of all trades is a master of none," which, in an ecological context, refers to the idea that generalists might be able to consume a wide range of resources but will not be particularly well adapted to any of them [17]. In this context, most studies show that specialized species tend to be smaller [18,19], more abundant, and more spatially restricted than their larger relatives [20,19]. However this pattern is not universal, and some studies report that such relationships do not exist for some insect clades [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these species differences, especially in terms of geographic ranges and environmental niche, when estimating occupancy is important as it can provide a more realistic depiction of abundance-occupancy relationships. For example, taking these species differences into account will improve our assessment of the effects of specialist and generalist species on abundanceoccupancy relationships [5,44] given that specialist species generally have narrower environmental niches and smaller geographic ranges than generalist species [45,46]. The positive relationship between species environmental niche and geographic range size [27,28] suggests that both factors are intrinsically related and are important to determine species occurrences.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that the higher energetic demand of larger species constrains them to occur in a narrow time period when optimal resources are available (Brown et al 2004;Ribeiro & Freitas 2011). Moreover, small-bodied species tend to have shorter lifespans, despite their wider temporal distribution, greater abundances, and narrower larval diet breadths (Hjalmarsson et al 2015;Freire-Jr. et al 2021.a;Sudta et al 2022). Although the association between diet breadth and temporal distribution is poorly understood in butter ies, our expectation is that the temporal distribution of smaller and more specialized butter y species will be less restricted throughout the year compared to their larger relatives (Pozo et al 2008;Ribeiro & Freitas 2011;Freire Jr. & Diniz 2015).…”
Section: Introductionmentioning
confidence: 96%